Performance of composite measures used in a trial of etanercept and methotrexate as monotherapy or in combination in psoriatic arthritis - Coates, L; Merola, JF; Mease, PJ; Ogdie, A; Gladman, DD; Strand, V; van Mens, L J.J.; Liu, L; Yen, PK; Collier, DH; Kricorian, G; Chung, JB; et al. (Oxford University Press, 2020)
Objectives To examine which composite measures are most sensitive to change when measuring psoriatic arthritis (PsA) disease activity, analyses compared the responsiveness of composite measures used in a 48-week randomized, controlled trial of MTX and etanercept in patients with PsA.